Polymer composition containing a blend of liquid crystalline polymers
Patent Information
- Application Number
- CN202580021935.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2024-03-20
- Filing Date
- 2025-03-05
- Publication Date
- 2026-10-30
AI Technical Summary
然而,由于聚酯共混物在加工过程中倾向于发生酯交换,导致分子重排、瞬态性质并最终降解,因此以这种方式回收利用废料的能力难以实现
[0034]无论特定的熔融共混条件如何,本发明的优点之一在于,对液晶聚合物的特定性质进行选择性控制可允许它们容易地共混,而不会因酯交换机理导致性能显著劣化。这一结果的一个主要益处是,液晶聚合物不需要是“原生的”聚合物,而是可以衍生自在聚合过程中或其他商业熔融配混过程中产生的废料。例如,在商业聚合和/或熔融配混过程中,聚合物的某些部分可能最终成为废料,其形式为废弃物、不合格制品、或在模制过程中的浇口和流道。
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_3
Abstract
Description
Related applications
[0001] This application is based on and claims priority to U.S. Provisional Patent Application No. 63 / 567,600, filed March 20, 2024, which is incorporated herein by reference. Background Technology
[0002] Liquid crystal polymers are polyesters used in a variety of high-performance applications, such as high-voltage connectors, medical products, camera modules, etc. These polymers are typically formed by acetylation of an aromatic monomer (e.g., with acetic anhydride) followed by heating the acetylated monomer in a reactor until the target molecular weight is reached. After polymerization, the molten polymer can be discharged from the reactor, cooled, and collected. Typically, the melt is discharged through a porous die to form a strip, which is then removed in a water bath, granulated, and dried. The resulting polymer can then be blended with other polymers and / or fillers. Unfortunately, a significant portion of the polymer obtained during the synthesis of liquid crystal polymers and / or their blending with other materials may be discarded as waste material. This waste material may include flakes, fluff, granules, fibers, etc., that cannot be formed into commercially suitable granules during the production process. Ideally, it is desirable to recycle this waste material in blends with other liquid crystal polymers, such as blends with virgin or other recycled liquid crystal polymers. However, the ability to recycle waste in this way is difficult to achieve because polyester blends tend to undergo transesterification during processing, leading to molecular rearrangement, transient properties, and eventual degradation. Therefore, there is a need for a polymer composition comprising blends of different liquid crystal polymers, wherein one or more polymers are derived from waste. Summary of the Invention
[0003] According to one embodiment of the present invention, a polymer composition is disclosed comprising a polymer matrix. The polymer matrix comprises at least one first liquid crystal polymer, the first liquid crystal polymer containing: an aromatic dicarboxylic acid repeating unit derived from 2,6-naphthalenedicarboxylic acid and optionally terephthalic acid, isophthalic acid, or combinations thereof; an aromatic diol repeating unit derived from hydroquinone, 4,4'-biphenol, or combinations thereof; and an aromatic hydroxycarboxylic acid repeating unit derived from 4-hydroxybenzoic acid, 6-hydroxy-2-naphthoic acid, or combinations thereof, wherein the repeating unit derived from 2,6-naphthalenedicarboxylic acid accounts for about 2 mol.% to about 30 mol.% of the first liquid crystal polymer. The polymer matrix further comprises at least one second liquid crystal polymer, the second liquid crystal polymer containing: aromatic dicarboxylic acid repeating units derived from 2,6-naphthalenedicarboxylic acid, terephthalic acid, isophthalic acid, or combinations thereof; aromatic diol repeating units derived from hydroquinone, 4,4'-biphenol, or combinations thereof; and aromatic hydroxycarboxylic acid repeating units derived from 4-hydroxybenzoic acid, 6-hydroxy-2-naphthoic acid, or combinations thereof, wherein the repeating units derived from 2,6-naphthalenedicarboxylic acid account for no more than about 0.5 mol.% of the second liquid crystal polymer. The ratio of aromatic diol repeating units of the first liquid crystal polymer to the aromatic diol repeating units of the second liquid crystal polymer is about 1 to about 8.
[0004] Other features and aspects of the invention are described in more detail below. Detailed Implementation
[0005] Those skilled in the art will understand that the discussion herein is merely a description of exemplary embodiments and is not intended to limit the broader aspects of the invention.
[0006] In general, the present invention relates to a polymer composition comprising a polymer matrix. The polymer matrix comprises a blend of one or more first liquid crystal polymers and one or more second liquid crystal polymers. By carefully controlling specific properties of the polymers, the inventors have discovered that the polymers can be melt-blended together without significant degradation of the thermal and mechanical properties of the resulting composition due to ester exchange mechanisms.
[0007] The polymer composition may exhibit, for example, high melt temperatures, such as about 240°C or higher, about 260°C or higher in some embodiments, about 290°C or higher in some embodiments, about 300°C to about 400°C in some embodiments, about 310°C to about 380°C in some embodiments, and about 320°C to about 370°C in some embodiments. Even at such melt temperatures, the ratio of the load flexural temperature (“DTUL”), a measure of short-term heat resistance, to the melt temperature may remain relatively high. For example, the ratio may be about 0.5 to about 1.00, about 0.6 to about 0.95 in some embodiments, and about 0.65 to about 0.85 in some embodiments. Specific DTUL values may be, for example, about 150°C or higher, about 200°C or higher in some embodiments, about 240°C or higher in some embodiments, about 245°C or higher in some embodiments, about 250°C or higher in some embodiments, and about 255°C to about 300°C in some embodiments. Such a high DTUL value particularly allows for the use of high-speed and reliable surface mount processes for mating molded parts formed from the polymer composition with other components. The heat resistance of the polymer composition can also be reflected by a “non-bubbling temperature,” which, as described in more detail below, can be about 240°C or higher, about 250°C or higher in some embodiments, about 260°C to about 300°C in some embodiments, and about 270°C to about 290°C in some embodiments.
[0008] In addition to good thermal properties, the polymer composition can also exhibit excellent mechanical properties. For example, the composition can exhibit relatively high tensile and / or flexural moduli, which allows it to maintain relative rigidity after being molded into thin parts. For example, the tensile modulus can be about 10,000 MPa or higher, measured at 23°C according to ISO 527:2019, in some embodiments about 8,000 MPa or higher, in some embodiments about 12,000 MPa to about 25,000 MPa, and in some embodiments about 14,000 MPa to about 20,000 MPa. The flexural modulus can also be about 10,000 MPa or higher, measured at 23°C according to ISO 178:2019, in some embodiments about 8,000 MPa or higher, in some embodiments about 12,000 MPa to about 25,000 MPa, and in some embodiments about 14,000 MPa to about 20,000 MPa. Of course, the polymer composition may also exhibit other favorable tensile and flexural properties. For example, the polymer composition may exhibit a tensile strength of about 10 MPa or higher, measured at 23°C according to ISO 527:2019, in some embodiments about 120 MPa to about 250 MPa, and in some embodiments about 120 MPa to about 180 MPa; and / or an elongation at break of about 0.5% or higher, in some embodiments about 0.6% to about 3.5%, and in some embodiments about 0.8% to about 3%. The polymer composition may also exhibit a flexural strength of about 100 MPa or higher, measured at 23°C according to ISO 178:2019, in some embodiments about 150 MPa to about 350 MPa, and in some embodiments about 180 MPa to about 250 MPa; and / or an elongation at break of about 0.5% or higher, in some embodiments about 0.6% to about 3.5%, and in some embodiments about 0.8% to about 3%. Impact strength may also be favorable. For example, the composition can exhibit approximately 3 kJ / m³ at 23°C, as determined according to ISO 179-1:2010. 2 Or higher notched impact strength of simply supported beams, approximately 5 to approximately 20 kJ / m in some embodiments. 2 In some embodiments, approximately 8 to approximately 15 kJ / m 2 .
[0009] In addition to the properties described above, the polymer composition can generally also be flame-retardant, even at relatively small thickness values, such as about 4 mm or less, about 0.2 to about 3.2 mm in some embodiments, about 0.4 to about 2.5 mm in some embodiments, and about 0.8 to about 2 mm in some embodiments. The flame-retardant properties of the composition can be characterized according to the UL94 vertical burning test procedure for “Flammability Testing of Plastic Materials for Parts of Equipment and Electrical Appliances” (February 28, 2023 edition). According to this procedure, for example, the composition can exhibit a V-0 rating at a part thickness of about 0.8 mm, and even at even smaller thicknesses, such as about 0.4 or about 0.2 mm. To achieve a V-0 rating, for example, the polymer composition generally does not exhibit drips that ignite lint. However, the polymer composition can even exhibit fewer than 3 non-ignitable lint drips, fewer than 2 non-ignitable lint drips in some embodiments, and fewer than 1 non-ignitable lint drips in some embodiments (e.g., 0 non-ignitable lint drips). The polymer composition may also exhibit a total flame time of about 50 seconds or less (t1 + t2), about 40 seconds or less in some embodiments, about 30 seconds or less in some embodiments, and about 20 seconds or less in some embodiments. The polymer composition may exhibit a V-0 rating before aging (“unaged V-0 rating”) and / or after aging at 70°C for 7 days (“aged V-0 rating”).
[0010] The polymer composition may also have a relatively smooth surface, characterized, for example, by a Rockwell surface hardness of about 25 or higher as determined according to ASTM D785-08 (2015) (M scale), about 35 or higher in some embodiments, about 45 or higher in some embodiments, and about 55 to about 100 in some embodiments.
[0011] In addition to the aforementioned favorable physical and thermal properties, the polymer composition also exhibits a low melt viscosity, which allows it to be used in certain types of ultrathin electronic components. For example, the polymer composition may have a melt viscosity of 1,000 seconds. -1 The melt viscosity is about 100 Pa-s or less, as determined according to ISO 11443:2021 at a temperature 15°C higher than the melting temperature of the composition (e.g., about 360°C for a melting temperature of about 345°C), in some embodiments about 1 to about 80 Pa-s, and in some embodiments about 5 to about 60 Pa-s.
[0012] Various embodiments of the present invention will now be described in more detail.
[0013] I. Polymer matrix
[0014] A. First liquid crystal polymer
[0015] As described above, the polymer matrix contains one or more first liquid crystal polymers, typically in amounts of about 1 wt.% to about 50 wt.% of the polymer matrix, in some embodiments about 2 wt.% to about 45 wt.% of the polymer matrix, and in some embodiments about 5 wt.% to about 40 wt.% of the polymer composition; and in some embodiments about 1 wt.% to about 20 wt.% of the polymer composition, in some embodiments about 2 wt.% to about 15 wt.% of the polymer composition, and in some embodiments about 3 wt.% to about 12 wt.% of the polymer composition. The first liquid crystal polymer may have a relatively high melting temperature, for example about 300°C or higher, in some embodiments about 310°C to about 400°C, in some embodiments about 320°C to about 380°C, and in some embodiments about 330°C to about 370°C.
[0016] The first liquid crystal polymer may contain: (ii) an aromatic dicarboxylic acid repeating unit derived from one or more aromatic dicarboxylic acids; (iii) an aromatic diol repeating unit derived from one or more aromatic diols; and (iv) an aromatic hydroxycarboxylic acid repeating unit derived from one or more aromatic hydroxycarboxylic acids. The aromatic dicarboxylic acid typically includes 2,6-naphthalenedicarboxylic acid (“NDA”) and may optionally include one or more other suitable aromatic dicarboxylic acids, such as terephthalic acid (“TA”), isophthalic acid (“IA”), diphenyl ether-4,4'-dicarboxylic acid, 1,6-naphthalenedicarboxylic acid, 2,7-naphthalenedicarboxylic acid, 4,4'-dicarboxybiphenyl, bis(4-carboxyphenyl) ether, bis(4-carboxyphenyl)butane, bis(4-carboxyphenyl)ethane, bis(3-carboxyphenyl) ether, bis(3-carboxyphenyl)ethane, etc., and their alkyl, alkoxy, aryl, and halogen substituents, and combinations thereof. The aromatic diol may include hydroquinone (“HQ”), 4,4'-biphenyl (“BP”), resorcinol, 2,6-dihydroxynaphthalene, 2,7-dihydroxynaphthalene, 1,6-dihydroxynaphthalene, 4,4'-dihydroxybiphenyl (or 4,4'-biphenyl), 3,3'-dihydroxybiphenyl, 3,4'-dihydroxybiphenyl, 4,4'-dihydroxydiphenyl ether, bis(4-hydroxyphenyl)ethane, etc., as well as their alkyl, alkoxy, aryl and halogen substituents, and combinations thereof. The aromatic hydroxycarboxylic acids may include 4-hydroxybenzoic acid (“HBA”), 6-hydroxy-2-naphthoic acid (“HNA”), 4-hydroxy-4'-biphenylcarboxylic acid, 2-hydroxy-6-naphthoic acid, 2-hydroxy-5-naphthoic acid, 3-hydroxy-2-naphthoic acid, 2-hydroxy-3-naphthoic acid, 4'-hydroxyphenyl-4-benzoic acid, 3'-hydroxyphenyl-4-benzoic acid, 4'-hydroxyphenyl-3-benzoic acid, etc., as well as their alkyl, alkoxy, aryl and halogen substituents, and combinations thereof.
[0017] The relative amounts of monomer components in the first liquid crystal polymer can be selectively controlled to help achieve desired performance. For example, in one embodiment, the first liquid crystal polymer may contain repeating units derived from NDA in an amount of about 2 mol.% to about 30 mol.%, in some embodiments about 3 mol.% to about 25 mol.%, and in some embodiments about 4 mol.% to about 22 mol.%. In addition to NDA, the first liquid crystal polymer may also contain other repeating units derived from aromatic dicarboxylic acids as described above. For example, in some embodiments, the first liquid crystal polymer may contain repeating units derived from TA and / or IA, in an amount of about 1 mol.% to about 30 mol.%, in some embodiments about 2 mol.% to about 25 mol.%, and in some embodiments about 5 mol.% to about 20 mol.%. The first liquid crystal polymer may also contain repeating units derived from HQ and / or BP, in an amount of about 5 mol.% to about 40 mol.%, in some embodiments about 10 mol.% to about 35 mol.%, and in some embodiments about 15 mol.% to about 30 mol.%. In addition to the components described above, the first liquid crystal polymer may contain repeating units derived from HBA, comprising about 30 mol.% to about 80 mol.% in some embodiments, about 35 mol.% to about 75 mol.% in some embodiments, and about 40 mol.% to about 70 mol.% in some embodiments. When used, the molar ratio of HBA to NDA can be selectively controlled within a specific range to help achieve desired performance, for example, about 0.5 to about 20, about 0.6 to about 18 in some embodiments, and about 1 to about 15 in some embodiments. Similarly, the total amount of NDA, TA, and IA may be equimolar or molar excess relative to the total amount of HQ and BP to help achieve desired performance. In other words, the ratio of the molar number of NDA, TA, and / or IA to the molar number of HQ and / or BQ may be about 1 or greater, about 1 to about 1.5 in some embodiments, and about 1.001 to about 1.3 in some embodiments.
[0018] Of course, other monomeric components may also be used in the first liquid crystal polymer, such as those derived from one or more aromatic amides (e.g., acetaminophen (“APAP”)) and / or aromatic amines (e.g., 4-aminophenol (“AP”), 3-aminophenol, 1,4-phenylenediamine, 1,3-phenylenediamine, etc.). When used, repeating units derived from aromatic amides (e.g., APAP) and / or aromatic amines (e.g., AP) typically constitute about 0.1 mol.% to about 20 mol.% of the polymer, about 0.5 mol.% to about 15 mol.% in some embodiments, and about 1 mol.% to about 10 mol.% in some embodiments. It should also be understood that various other monomeric repeating units may be introduced into the polymer. For example, in some embodiments, the polymer may contain one or more repeating units derived from non-aromatic monomers, such as aliphatic or cycloaliphatic hydroxycarboxylic acids, dicarboxylic acids, diols, amides, amines, etc. Of course, in other embodiments, the polymer may be "fully aromatic" because it lacks repeating units derived from non-aromatic (e.g., aliphatic or cycloaliphatic) monomers.
[0019] B. Second liquid crystal polymer
[0020] The polymer matrix further comprises one or more second liquid crystal polymers, typically in amounts of about 50 wt.% to about 99 wt.% of the polymer matrix, in some embodiments about 55 wt.% to about 98 wt.% and in some embodiments about 60 wt.% to about 95 wt.%; and in some embodiments about 20 wt.% to about 70 wt.% of the polymer composition, in some embodiments about 25 wt.% to about 65 wt.% and in some embodiments about 30 wt.% to about 60 wt.%. The second liquid crystal polymer may have a relatively high melting temperature, for example about 300°C or higher, in some embodiments about 310°C to about 400°C, in some embodiments about 320°C to about 380°C, and in some embodiments about 330°C to about 370°C. The second liquid crystal polymer may contain: (ii) an aromatic dicarboxylic acid repeating unit derived from one or more aromatic dicarboxylic acids; (iii) an aromatic diol repeating unit derived from one or more aromatic hydroxycarboxylic acids, as described in more detail above.
[0021] The relative amounts of monomer components in the second liquid crystal polymer can be selectively controlled to help achieve desired performance. For example, in one embodiment, the second liquid crystal polymer may contain repeating units derived from TA and / or IA in amounts from about 2 mol.% to about 30 mol.%, in some embodiments from about 3 mol.% to about 25 mol.%, and in some embodiments from about 4 mol.% to about 22 mol.%. However, in contrast to the first liquid crystal polymer, the second liquid crystal polymer typically does not contain repeating units derived from NDA, or contains at least a relatively small amount of repeating units derived from NDA, such as about 0.5 mol.% or less, in some embodiments about 0.3 mol.% or less, and in some embodiments from 0 mol.% to about 0.2 mol.%. The second liquid crystal polymer may also contain repeating units derived from one or more aromatic diols. Typically, the aromatic diol repeating units in the first liquid crystal polymer are present in a greater amount than those in the second liquid crystal polymer, such that the ratio of the aromatic diol repeating units of the first liquid crystal polymer to those of the second liquid crystal polymer is selectively controlled in the range of about 1 to about 8, in some embodiments about 1.1 to about 5, and in some embodiments about 1.2 to about 4. For example, the total amount of HQ and / or BP may account for about 1 mol.% to about 30 mol.% of the second liquid crystal polymer, in some embodiments about 2 mol.% to about 25 mol.%, and in some embodiments about 5 mol.% to about 20 mol.%.
[0022] The second liquid crystal polymer may also contain repeating units derived from HBA and / or HNA, in total quantities of about 30 mol.% to about 80 mol.%, and in some embodiments about 35 mol.% to about 75 mol.%, and in some embodiments about 40 mol.% to about 70 mol.%. When used, the molar ratio of HBA to HNA can be selectively controlled within a specific range to help achieve desired performance, for example about 2 to about 20, in some embodiments about 4 to about 18, and in some embodiments about 5 to about 15. Similarly, the total amounts of NDA, TA, and IA may be equimolar or molar excess relative to the total amounts of HQ and BP to help achieve desired performance. In other words, the ratio of the molar number of NDA, TA, and / or IA to the molar number of HQ and / or BQ may be about 1 or greater, in some embodiments about 1 to about 2, and in some embodiments about 1.1 to about 1.6. Other monomeric components may also be used in the second liquid crystal polymer, such as those described above. For example, in one embodiment, the second liquid crystal polymer may contain repeating units derived from APAP in an amount of about 0.1 mol.% to about 20 mol.%, in some embodiments about 0.5 mol.% to about 15 mol.%, and in some embodiments about 1 mol.% to about 10 mol.%.
[0023] C. Other polymers
[0024] In some embodiments, the polymer matrix is formed entirely of polymers of the aforementioned categories—that is, the first liquid crystal polymer and the second liquid crystal polymer. Of course, additional polymers, such as liquid crystal polymers, may be used in the polymer matrix if desired. For example, in one particular embodiment, the polymer matrix may contain one or more third liquid crystal polymers, typically in amounts from about 1 wt.% to about 35 wt.% of the polymer matrix, in some embodiments from about 2 wt.% to about 30 wt.%, and in some embodiments from about 5 wt.% to about 25 wt.%; and in some embodiments from about 1 wt.% to about 25 wt.% of the polymer composition, in some embodiments from about 2 wt.% to about 20 wt.%, and in some embodiments from about 5 wt.% to about 15 wt.%. The melting temperature of the third liquid crystal polymer may be lower than that of the first and second liquid crystal polymers. For example, the melting temperature of the third liquid crystal polymer may be from about 250°C to about 350°C, in some embodiments from about 260°C to about 340°C, and in some embodiments from about 280°C to about 320°C.
[0025] The third liquid crystal polymer may contain repeating units of aromatic hydroxycarboxylic acids derived from one or more aromatic hydroxycarboxylic acids, as described in more detail above. The third liquid crystal polymer may, for example, contain repeating units derived from HBA and / or HNA. In some embodiments, the polymer may be formed entirely of such repeating units. For example, repeating units derived from HBA may comprise about 40 mol.% to about 90 mol.% of the third liquid crystal polymer, and in some embodiments about 50 mol.% to about 85 mol.% of the third liquid crystal polymer, and in some embodiments about 60 mol.% to about 80 mol.% of the third liquid crystal polymer; and repeating units derived from HNA may comprise about 10 mol.% to about 60 mol.% of the third liquid crystal polymer, and in some embodiments about 15 mol.% to about 50 mol.% of the third liquid crystal polymer, and in some embodiments about 20 mol.% to about 40 mol.% of the third liquid crystal polymer. The molar ratio of HBA to HNA can also be selectively controlled within a specific range to help achieve desired performance, for example about 1 to about 10, about 1.5 to about 8 in some embodiments, and about 2 to about 5 in some embodiments. In contrast to the first and second liquid crystal polymers, the third liquid crystal polymer typically does not contain repeating units derived from NDA, TA, IA, BP and / or HQ, or contains at least a relatively small amount of such repeating units, for example, about 10 mol.% or less, about 5 mol.% or less in some embodiments, and about 0 mol.% to about 2 mol.% in some embodiments.
[0026] Regardless of the specific composition, the liquid crystal polymers (e.g., first, second, and / or third liquid crystal polymers) can be prepared by first introducing aromatic monomers for forming ester repeating units (e.g., aromatic hydroxycarboxylic acids, aromatic dicarboxylic acids, etc.) and / or other repeating units (e.g., aromatic diols, aromatic amides, aromatic amines, etc.) into a reaction vessel to initiate a polycondensation reaction. The specific conditions and steps employed in such reactions are well known and can be described in more detail in U.S. Patent No. 4,161,470 to Calundann; U.S. Patent No. 5,616,680 to Linstid, III et al.; U.S. Patent No. 6,114,492 to Linstid, III et al.; U.S. Patent No. 6,514,611 to Shepherd et al.; and WO 2004 / 058851 to Waggoner. There are no particular limitations on the reaction vessels used, although those commonly used for reactions involving high-viscosity fluids are generally preferred. Examples of such reaction vessels may include stirred tank type equipment with a stirrer having a variable-shape stirring paddle (e.g., anchor type, multi-stage type, spiral ribbon type, spiral shaft type, etc., or variations thereof). Other examples of such reaction vessels may include mixing equipment commonly used for resin kneading, such as kneaders, roller mills, Banbury mixers, etc.
[0027] If desired, the reaction can be carried out by monomer acetylation as known in the art. This can be achieved by adding an acetyling agent (e.g., acetic anhydride) to the monomer. Acetylation is typically initiated at a temperature of about 90°C. In the initial stages of acetylation, reflux can be employed to keep the gas phase temperature below the temperature at which the acetic acid byproducts and anhydride begin to distill. The temperature during acetylation is typically between 90°C and 150°C, and in some embodiments, between about 110°C and about 150°C. If reflux is used, the gas phase temperature is typically above the boiling point of acetic acid, but kept low enough to retain residual acetic anhydride. For example, acetic anhydride vaporizes at a temperature of about 140°C. Therefore, providing the reactor with a gas phase reflux at a temperature of about 110°C to about 130°C is particularly desirable. To ensure substantially complete reaction, an excess of acetic anhydride can be used. The amount of excess anhydride will vary depending on the specific acetylation conditions employed, including the presence or absence of reflux. It is not uncommon to use an excess of acetic anhydride of about 1 to about 10 molar percentages based on the total number of moles of hydroxyl groups present in the reactants.
[0028] Acetylation can be carried out in a separate reaction vessel or it can be carried out in situ within a polymerization reactor. When a separate reaction vessel is used, one or more monomers can be introduced into the acetylation reactor and subsequently transferred to the polymerization reactor. Similarly, one or more monomers can be introduced directly into the reaction vessel without pre-acetylation. In addition to the monomers and optional acetylation agents, other components may also be included in the reaction mixture to help promote polymerization. For example, catalysts may be optionally used, such as metal salt catalysts (e.g., magnesium acetate, tin(I) acetate, tetrabutyl titanate, lead acetate, sodium acetate, potassium acetate, etc.) and organic compound catalysts (e.g., N-methylimidazole). Such catalysts are typically used in amounts of about 50 to about 500 parts per million based on the total weight of the repeating unit precursors. When a separate reactor is used, it is generally desirable to apply the catalyst to the acetylation reactor rather than the polymerization reactor, although this is by no means a requirement.
[0029] The reaction mixture is typically heated to elevated temperatures within a polymerization reactor to initiate melt polycondensation of the reactants. Polycondensation can occur, for example, in a temperature range of about 200°C to about 400°C. For instance, a suitable technique for forming liquid crystal polymers may include charging a precursor monomer and acetic anhydride into a reactor, heating the mixture to a temperature of about 90°C to about 150°C to acetylate the hydroxyl groups of the monomer (e.g., to form acetoxy groups), and then raising the temperature to about 200°C to about 400°C for melt polycondensation. Volatile byproducts of the reaction (e.g., acetic acid) can also be removed as the final polymerization temperature approaches, thereby readily achieving the desired molecular weight. The reaction mixture is typically stirred during polymerization to ensure good heat and mass transfer, as well as good material homogeneity. The rotational speed of the stirrer can vary during the reaction, but is typically between about 10 and about 100 rpm, and in some embodiments about 20 to about 80 rpm. To increase the molecular weight in the melt, the polymerization reaction may also be carried out under a vacuum, the application of which helps remove volatiles formed during the final stages of polycondensation. A vacuum can be created by applying suction pressure, for example in the range of about 5 to about 30 pounds per square inch (“psi”), and in some implementations about 10 to about 20 psi.
[0030] Typically, the molten polymer is discharged from the reactor when it reaches the desired melt viscosity. As is known in the art, this can be related to the torque of the agitator. For example, after the agitator torque reaches a predetermined value, nitrogen can be introduced into the reactor, thereby converting the reduced pressure conditions from atmospheric pressure to pressurized conditions, thereby discharging the resulting polymer from the reactor, typically through an extrusion orifice equipped with a die of the desired configuration, cooling, and collecting. The melt is typically discharged through a porous die to form a strip, which is then removed in a water bath, granulated, and dried.
[0031] While not always necessary or desirable, melt-polymerized polymers can be further subjected to solid-state polymerization to increase their molecular weight and achieve desired melt viscosity. Solid-state polymerization can be carried out in the presence of a gas (e.g., air, inert gas, etc.). Suitable inert gases may include, for example, nitrogen, helium, argon, neon, krypton, xenon, and combinations thereof. The solid-state polymerization reactor can have virtually any design, as long as it allows the polymer to maintain the desired residence time at the desired solid-state polymerization temperature. Examples of such reactors may be those with fixed beds, static beds, moving beds, fluidized beds, etc. The temperature at which solid-state polymerization takes place can vary, but is typically in the range of about 200°C to about 400°C. The polymerization time will, of course, vary depending on the temperature and the target molecular weight. However, in most cases, the solid-state polymerization time will be about 2 to about 12 hours, and in some embodiments about 4 to about 10 hours.
[0032] II. Melt blending
[0033] Liquid crystal polymers can be melt-processed or blended together to form a polymer matrix. The components can be supplied individually or in combination to an extruder including at least one screw rotatably mounted and housed within a barrel (e.g., a cylindrical barrel), and a feed section and a melt section downstream of the feed section can be defined along the length of the screw. The extruder can be a single-screw or twin-screw extruder. The screw speed can be selected to achieve desired residence time, shear rate, melt processing temperature, etc. For example, the screw speed can be about 50 to about 800 rpm, about 70 to about 150 rpm in some embodiments, and about 80 to about 120 rpm in some embodiments. The apparent shear rate during the melt blending process can also be about 100 seconds. -1 Approximately 10,000 seconds -1 In some implementations, approximately 500 seconds -1 Approximately 5000 seconds -1 And in some implementations, approximately 800 seconds -1 Approximately 1200 seconds -1 The apparent shear rate is equal to 4Q / πR. 3 Where Q is the volumetric flow rate of the polymer melt (m³ / s). 3 / s”, where R is the radius (“m”) of the capillary (e.g., extruder die) through which the molten polymer flows.
[0034] Regardless of specific melt blending conditions, one of the advantages of this invention is that selective control over specific properties of liquid crystal polymers allows them to be easily blended without significant performance degradation due to ester exchange mechanisms. A major benefit of this result is that the liquid crystal polymers do not need to be "native" polymers, but can be derived from waste generated during polymerization or other commercial melt blending processes. For example, during commercial polymerization and / or melt blending, portions of the polymer may end up as waste, defective articles, or gates and runners in the molding process.
[0035] However, typically at least a majority of the waste material is derived from polymers collected during the granulation process (e.g., discharged from reactors, cut, graded, etc.). Once collected, the waste polymer can be used as is, or alternatively, reformed into pellets for melt blending. For example, in one embodiment, the pellets can be formed by first grinding the collected waste polymer using known grinding equipment (wet or dry), such as jaw crushers, gyratory crushers, cone crushers, roller crushers, impact crushers, hammer crushers, split-cutters, rod mills, ball mills, vibrating rod mills, vibrating ball mills, disc mills, roller mills, impact mills, disc mills, stirred mills, fluid energy mills, air jet mills, etc. For example, air jet mills typically involve the use of shears or pulverizers, where the polymer is accelerated by an airflow and pulverized by impact. Any type of air jet mill design can be employed, such as dual-convective (counter-jet) and helical (disc) fluid energy mills. The gas and particle flow can be simple, flowing in a helical manner, or have more complex flow patterns, but essentially the particles collide with each other or with collision surfaces. In some embodiments, it may be desirable to grind the polymer in the presence of a cryogenic fluid (e.g., dry ice, liquid carbon dioxide, liquid argon, liquid nitrogen, etc.) to create a cryogenic environment in the system. The cryogenic environment cools the polymer below its glass transition point to facilitate grinding in a mill that applies impact or shear (e.g., an air jet mill). Regardless of the technique used, the ground waste particles can have any desired average particle size, but are typically from about 0.1 to about 250 micrometers, from about 0.2 to about 150 micrometers in some embodiments, and from about 1 to about 100 micrometers in some embodiments, as measured by optical microscopy. The waste particles can then be re-granulated into thermoplastic resin pellets according to methods known in the art. For example, the waste particles can be heated to the form of molten polymer and then extruded through a die set at the discharge outlet into a strip. The strip can be cooled by a water bath, cooled, and then cut into pellet shapes after solidification. An example of suitable granulation equipment for this purpose is an "underwater melt cutter," which is described in more detail in U.S. Patent No. 7,658,874 to Jackson et al. and U.S. Patent Publication No. 2010 / 0102467 to Waggoner et al., both of which are incorporated herein by reference in their entirety. The granules can then be dried (e.g., in an oven) before being combined with other polymers and / or additives.
[0036] Therefore, in some embodiments of the present invention, the first liquid crystal polymer, the second liquid crystal polymer, and / or the third liquid crystal polymer can be derived from waste polymers in the manner described above. That is, such polymers can be entirely or at least substantially derived from a method comprising the steps of: collecting waste (recycled polymer), grinding the waste into granules, and then regranulating the granules for subsequent melt blending with other polymers and / or additives. For example, in one embodiment, the polymer matrix may, in some cases, be entirely formed from waste. In other embodiments, at least a portion of the polymer matrix may be formed from waste, for example, about 10 wt.% or more, about 20 wt.% to about 80 wt.% in some embodiments, and about 30 wt.% to about 70 wt.% in some embodiments.
[0037] III. Packing
[0038] In some embodiments, the polymer composition may contain only the polymer matrix. Of course, in addition to the polymer matrix itself, it should be understood that one or more fillers, as known in the art, may be incorporated into the polymer matrix during melt blending. When used, such fillers typically constitute from about 1 wt.% to about 70 wt.% of the polymer composition, from about 10 wt.% to about 60 wt.% in some embodiments, and from about 20 wt.% to about 55 wt.% in some embodiments, while the polymer matrix may also constitute from about 30 wt.% to about 99 wt.% of the polymer composition, from about 40 wt.% to about 90 wt.% in some embodiments, and from about 45 wt.% to about 80 wt.% in some embodiments.
[0039] For example, in one embodiment, reinforcing fibers may also be used in the polymer composition in an amount of about 5 wt.% to about 50 wt.% of the polymer composition, in some embodiments about 8 wt.% to about 40 wt.% of the polymer composition, and in some embodiments about 10 wt.% to about 35 wt.% of the polymer composition. Examples of such fibers may include, for example, polymer fibers, metal fibers, carbon fibers (e.g., graphite, carbides, etc.), inorganic fibers, and combinations thereof. Inorganic fibers may be particularly suitable, for example, those derived from glass; etc. Glass fibers may be particularly suitable for the present invention, for example, those formed from E-glass, A-glass, C-glass, D-glass, AR-glass, R-glass, S1-glass, S2-glass, and mixtures thereof. If desired, a sizing agent or other coatings known in the art may be provided to the reinforcing fibers. The average diameter of the fibers may be about 1 to about 50 micrometers, in some embodiments about 5 to about 45 micrometers, and in some embodiments about 10 to about 35 micrometers, as measured by known optical microscopy techniques. The fibers can be continuous fibers or chopped fibers, for example, those with a length of about 1 to about 15 mm, and in some embodiments about 2 to about 6 mm.
[0040] In addition to reinforcing fibers, the polymer composition may also contain particulate fillers distributed within the polymer matrix, in an amount of about 5 wt.% to about 50 wt.% of the polymer composition, in some embodiments about 8 wt.% to about 40 wt.% of the polymer composition, and in some embodiments about 10 wt.% to about 35 wt.% of the polymer composition. If desired, the particles may also have a high specific surface area, for example about 1 m² / g (m²). 2 / g) to about 50m 2 / g, in some embodiments approximately 1.5m 2 / g to approximately 25m 2 / g, and in some embodiments about 2m 2 / g to approximately 15m 2 / g. Specific surface area can be determined by physical gas adsorption (BET) method (nitrogen as the adsorbed gas) according to DIN 66131:1993. Moisture content can also be relatively low, for example, determined according to ISO 787-2:1981 at a temperature of 105°C, of about 5% or less, in some embodiments about 3% or less, and in some embodiments about 0.1% to about 1%. Suitable particulate particles may include those formed, for example, from inorganic materials, such as barium sulfate, calcium sulfate, calcium carbonate, talc, etc. For example, in one embodiment, the particulate filler may include talc particles. When used, the median particle size of the talc particles may be, for example, about 3 to about 15 micrometers, in some embodiments about 4 to about 12 micrometers, and in some embodiments about 5 to about 10 micrometers, as determined by laser diffraction according to ISO 13320:2020 (e.g., using a Horiba LA-960 particle size analyzer) and / or by sedimentation analysis (e.g., Sedigraph 5120).
[0041] In addition to the aforementioned particulate filler particles (e.g., talc, barium sulfate, etc.), other types of mineral fillers may be used in amounts from about 1 wt.% to about 40 wt.% of the polymer composition, from about 2 wt.% to about 35 wt.% in some embodiments, and from about 5 wt.% to about 30 wt.% in some embodiments. Suitable non-particulate mineral fillers may include, for example, flake-shaped mineral particles, mineral fibers (e.g., wollastonite fibers), etc. For example, flake-shaped mineral particles with a relatively high aspect ratio (e.g., average diameter divided by average thickness) may be used, for example, about 4 or greater, from about 8 or greater in some embodiments, and from about 10 to about 500 in some embodiments. In such embodiments, the average diameter of the particles may be, for example, from about 5 micrometers to about 200 micrometers, from about 8 micrometers to about 150 micrometers in some embodiments, and from about 10 micrometers to about 100 micrometers in some embodiments. The average thickness can also be about 2 micrometers or less, about 5 nanometers to about 1 micrometer in some embodiments, and about 20 nanometers to about 500 nanometers in some embodiments, as determined using laser diffraction techniques according to ISO 13320:2020 (e.g., using a Horiba LA-960 particle size analyzer). Suitable platy mineral particles can be formed from natural and / or synthetic silicate minerals, such as mica, halloysite, kaolinite, illite, montmorillonite, vermiculite, palygorskite, pyrophyllite, calcium silicate, aluminum silicate, wollastonite, etc. Mica is particularly suitable. Any form of mica can generally be used, including, for example, muscovite (KAl2(AlSi3)O). 10 (OH)2), biotite (K(Mg,Fe)3(AlSi3)O 10 (OH)2), Phlogopite (KMg3(AlSi3)O 10(OH)2), Lithium mica (K(Li,Al)2₋3(AlSi3)O 10 (OH)2), glauconite ((K,Na)(Al,Mg,Fe)2(Si,Al)4O 10 (OH)2), etc. Mica based on muscovite is particularly suitable for the polymer compositions described above.
[0042] The polymer composition may also contain a variety of other additives, such as impact modifiers, lubricants, pigments (e.g., carbon black), antioxidants, stabilizers, surfactants, waxes, flame retardants, nucleating agents (e.g., boron nitride), conductive fillers, laser-direct additives, and other materials added to enhance performance and processability. For example, in one embodiment, the polymer composition may be “laser-activated” because it contains laser-activated additives that can be activated by a laser direct forming (“LDS”) process. In such a process, the additives are exposed to a laser, causing metal release. The laser thus patterns the conductive elements onto the part, leaving a rough surface containing embedded metal particles. These particles act as nuclei for crystal growth in subsequent electroplating processes (e.g., copper plating, gold plating, nickel plating, silver plating, zinc plating, tin plating, etc.). When used, the laser-activated additive typically comprises about 0.5 wt.% to about 20 wt.% of the polymer composition, about 1 wt.% to about 15 wt.% in some embodiments, about 2 wt.% to about 10 wt.% in some embodiments, and about 4 wt.% to about 7 wt.% in some embodiments. The laser-activated additive may comprise spinel crystals, which may comprise two or more metal oxide cluster configurations within a definable crystal formation. For example, the overall crystal formation may have the following general formula:
[0043] AB2O4
[0044] in,
[0045] A is a divalent metal cation, such as cadmium, chromium, manganese, nickel, zinc, copper, cobalt, iron, magnesium, tin, titanium, and combinations thereof; and
[0046] B is a metal cation with a trivalent state, such as chromium, iron, aluminum, nickel, manganese, tin, and combinations thereof.
[0047] Typically, A in the above formula provides the main cationic component of the first metal oxide cluster, and B provides the main cationic component of the second metal oxide cluster. These oxide clusters may have the same or different structures. For example, in one embodiment, the first metal oxide cluster has a tetrahedral structure, and the second metal oxide cluster has an octahedral cluster. In any case, these clusters may collectively provide a single identifiable crystal type structure with increased sensitivity to electromagnetic radiation. Examples of suitable spinel crystals include, for example, MgAl2O4, ZnAl2O4, FeAl2O4, CuFe2O4, CuCr2O4, MnFe2O4, NiFe2O4, TiFe2O4, FeCr2O4, MgCr2O4, etc. Copper chromium oxide (CuCr2O4) is particularly suitable for this invention and is available from Shepherd Color Co. under the designations 1G or LD 14 (Shepherd Color Co.).
[0048] IV. Products
[0049] In general, the polymer composition is well-suited for a wide range of products, particularly electronic components such as electrical connectors, camera modules, antenna modules, etc. Examples of products that may contain such electronic components (e.g., connectors, camera modules, etc.) may include, for example, cellular phones, laptop computers, small portable computers (e.g., ultra-portable computers, netbooks, and tablets), wristwatches, pendant devices, headphones and earphones, media players with wireless communication capabilities, handheld computers (sometimes also called personal digital assistants), remote controls, GPS devices, handheld gaming devices, battery covers, speakers, camera modules, integrated circuits (e.g., SIM cards), electronic device housings, electrical control devices, circuit breakers, switches, power electronic devices, printer parts, etc.
[0050] For example, in one embodiment, the polymer composition can be used in molding interconnect devices. For example, the device may contain a substrate comprising the polymer composition of the present invention and one or more conductive elements electroplated thereon. The substrate can be formed using a variety of different molding techniques. Suitable techniques may include, for example, injection molding, low-pressure injection molding, extrusion compression molding, gas injection molding, foam injection molding, low-pressure gas injection molding, low-pressure foam injection molding, gas extrusion compression molding, foam extrusion compression molding, extrusion molding, foam extrusion molding, compression molding, foam compression molding, gas compression molding, insert molding, pin insert molding, etc. For example, an injection molding system including a mold into which the polymer composition can be injected can be used. The timing inside the syringe can be controlled and optimized so that the polymer matrix is not pre-cured. When the cycle time is reached and the cylinder is full to discharge, the composition can be injected into the mold cavity using a piston. Compression molding systems can also be used. As with injection molding, molding the polymer composition into the desired article also occurs within the mold. Any known technique, such as placing the composition into the compression mold by an automated robotic arm, can be used. The mold temperature can be maintained at or above the solidification temperature of the polymer matrix for the required duration to allow solidification. The molded product can then be solidified by bringing it to a temperature below its melt temperature. The resulting product can then be demolded. The cycle time for each molding process can be adjusted to suit the polymer matrix to achieve optimal bonding and improve overall process yield.
[0051] Conductive elements can be deposited on a substrate using any of a variety of known electroplating techniques, such as laser direct forming, electroplating, electroless plating, digital printing, aerosol jet printing, etc. For example, when laser-activated additives are present, laser activation can lead to a physicochemical reaction in which spinel crystals are cleaved to release metal atoms. These metal atoms can act as nuclei for metallization (e.g., reduction copper plating). The laser also produces a microscopically irregular surface and ablates the polymer matrix, creating numerous micro-pits and undercuts in which copper can be anchored during metallization. The conductive element may contain one or more conductive materials, such as metals, such as gold, silver, nickel, aluminum, copper, and mixtures or alloys thereof. For example, in one embodiment, the conductive element may include copper and / or nickel (e.g., pure or alloys thereof). If desired, a seed layer may first be formed on the substrate to facilitate the electroplating process. The method for forming the desired interconnect pattern may vary according to manner known to those skilled in the art. For example, in some cases, a pattern may first be formed on the substrate surface based on the desired circuit interconnect pattern.
[0052] Molded interconnect devices are particularly suitable for antenna modules. In this embodiment, the plated conductive elements can be antenna elements (e.g., antenna resonant elements). The conductive elements can form various types of antennas, such as antennas with resonant elements, formed from patch antenna elements, inverted-F antenna elements, closed and open slot antenna elements, loop antenna elements, monopoles, dipoles, planar inverted-F antenna elements, hybrids of these designs, etc. In one specific embodiment, for example, the antenna module can include a shielding member configured to cover communication circuitry and a dielectric on which one or more antenna elements are disposed. The shielding member can include a substrate plated with a metallic coating. If desired, the dielectric and / or substrate of the shielding member can contain the polymer composition of the present invention. In some embodiments, interconnecting members can also be used in the antenna module, electrically connected to the communication circuitry and antenna elements. The interconnecting members can also include a substrate plated with a metallic coating. If desired, the substrate of the interconnecting member can contain the polymer composition of the present invention.
[0053] The present invention can be better understood by referring to the following embodiments and test methods.
[0054] Test methods
[0055] Melt viscosity: Melt viscosity (Pa-s) can be determined according to ISO 11443:2021 at 400 s. -1 Or 1000s -1 The measurements were performed using a Dynisco LCR7001 capillary rheometer at shear rates and at temperatures 15°C higher than the melting temperature (e.g., approximately 325°C). The rheometer orifice (dial) can have a diameter of 1 mm, a length of 20 mm, an L / D ratio of 20.1, and an inlet angle of 180°. The cylinder diameter can be 9.55 mm ± 0.005 mm, and the rod length can be 233.4 mm.
[0056] Melting Temperature: The melting temperature (“Tm”) can be determined by differential scanning calorimetry (“DSC”) as known in the art. The melting temperature is the peak melting temperature of the differential scanning calorimetry (DSC) as determined according to ISO 11357-3:2018. DSC measurements are performed using a TA Q2000 instrument according to ISO standard 10350, with the sample heated and cooled at a rate of 20 °C / min.
[0057] Load flexure temperature (“DTUL”): Load flexure temperature can be determined according to ISO 75-2:2013 (technically equivalent to ASTM D648). More specifically, a test strip specimen with a length of 80 mm, a thickness of 10 mm, and a width of 4 mm is subjected to a three-point edge bending test, wherein the specified load (maximum outer fiber stress) is 1.8 MPa. The specimen can be immersed in a silicone oil bath, and the temperature is increased at a rate of 2 °C / min until it deflects 0.25 mm (0.32 mm for ISO Test No. 75-2:2013).
[0058] Tensile modulus, tensile stress, and tensile elongation: Tensile properties can be tested according to ISO 527:2019 (technically equivalent to ASTM D638). Modulus and strength measurements can be performed on identical test strips with a length of 80 mm, a thickness of 10 mm, and a width of 4 mm. The test temperature can be 23°C, and the test speed can be 1 or 5 mm / min.
[0059] Flexural modulus, flexural stress, and flexural elongation: Flexural properties can be tested according to ISO 178:2019 (technically equivalent to ASTM D790). This test can be performed over a 64 mm support span. The test can be performed on the center portion of an uncut ISO 3167 multipurpose bar. The test temperature can be 23°C, and the test speed can be 2 mm / min.
[0060] Simply supported beam impact strength: The performance of simply supported beams can be tested according to ISO 179-1:2010 (technically equivalent to ASTM D256-10, Method B). This test can be performed using a Type 1 specimen (80 mm in length, 10 mm in width, and 4 mm in thickness). When testing notched impact strength, the notch can be a Type A notch (0.25 mm base circle radius). The specimen can be cut from the center of a multi-purpose bar using a single-tooth milling machine. The test temperature can be 23°C.
[0061] Rockwell Hardness: Rockwell hardness is a measure of a material's resistance to indentation and can be determined according to ASTM D785-08 (2015) (M scale). The test is performed by first pressing a steel ball indenter into the material surface using a specified initial load. The load is then increased to a specified master load and then reduced back to the original initial load. Rockwell hardness is a measure of the net increase in indentation depth, calculated by dividing the indentation depth by the scale graduation and then subtracting from 130.
[0062] Non-bubbling temperature: To test foaming resistance, test bars of 127 × 12.7 × 0.8 mm were molded at a temperature 5°C to 10°C higher than the melt temperature of the polymer resin (determined by DSC). Ten (10) bars were then passed through the heating chamber of a reflow oven with a predetermined temperature profile, then removed, cooled to ambient conditions, and examined for any bubbling that may have formed (i.e., surface deformation). The predetermined temperature profile started at 250°C and increased in 10°C increments until bubbling was observed on one or more test bars. The highest temperature at which no visible bubbling was observed on all ten (10) bars was determined as the “non-bubbling temperature” of the test material.
[0063] Flame retardancy: Flame retardancy was determined according to the UL 94 Vertical Burning Test Procedure, “Flammability Test of Plastic Materials for Parts of Equipment and Electrical Appliances” (28 February 2023 edition), which is now consistent with IEC 60707, 60695-11-10 and 60695-11-20 and ISO 9772 and 9773. In the test, two groups of five samples (ten in total) were used, with samples having a length of 125 mm, a width of 13 mm, and a thickness within the desired range (e.g., 0.8 mm, 0.4 mm, or 0.2 mm). Both groups of samples were conditioned before and after aging. For the unaged test, each thickness was tested after conditioning at 23°C and 50% relative humidity for 48 hours. For the aged test, five (5) samples of each thickness were tested after conditioning at 70°C for 168 hours and then cooling in a desiccator at room temperature for at least 4 hours. To begin testing, position the sample holder so that the sample is held at least 425 mm above the work surface. Place a cotton wadding (e.g., less than 6 mm thick) directly below the fixture to ensure coverage of a 50 mm × 50 mm area. Position the top 6 mm of the sample vertically in the fixture and adjust the holder so that the bottom edge of the sample is 300 ± 10 mm above the cotton wadding. Once in place, apply a flame for ten (10) seconds and then remove it until the flame stops. Apply the flame again for another ten (10) seconds and then remove it. If dripping occurs, it should fall onto the cotton wadding below the sample. Record the time when the flame stops burning as “t1”, and then apply the burner again. Record the time when the flame ends as “t2”. Record the time when incandescent burning ends as “t3”. Then compare the results with the UL94 flame retardancy rating based on the criteria provided in the table below.
[0064]
[0065] Examples 1-7
[0066] Examples 1 through 7 are formed from various percentages of a first liquid crystal polymer (“LCP 1”), a second liquid crystal polymer (“LCP 2”), a third liquid crystal polymer (“LCP 3”), glass fiber, talc, and a laser direct molding concentrate (“LDS concentrate”), wherein the laser direct molding concentrate contains 30 wt.% copper chromite black spinel crystals and 70 wt.% liquid crystal polymer (“LCP 2a”). LCP 1 is formed from approximately 61.5% HBA, 13.5% TA, 9.6% BP, 9.6% HQ, and 5.8% NDA, and has a melting temperature of approximately 335°C. LCP 2 is formed from approximately 60% HBA, 5% HNA, 12.5% BP, 17.5% TA, and 5% APAP, and has a melting temperature of approximately 338°C. LCP 3 is formed from 73% HBA and 27% HNA, and has a melting temperature of approximately 280°C. LCP 1, LCP 2, and LCP 3 are each derived from waste collected during the commercial granulation process of their respective polymers. The waste is ground into granules (1–2 lbs, for 15 minutes), regranulated, and then dried at 275°C for 4–6 hours before being melt-blended with glass fiber, talc, and LDS concentrate. LCP 2a has the same composition as LCP 2 but is not derived from plant waste. Specific formulations are described in more detail in Table 1 below.
[0067] Table 1: Formula
[0068]
[0069] The thermal properties, mechanical properties, and flame retardancy of samples 1-7 were tested. The results are presented in Tables 2-3 below.
[0070] Table 2: Thermal and Mechanical Properties
[0071]
[0072] Table 3: Unaged flame retardancy at 0.8mm
[0073]
[0074] Examples 8-12
[0075] Examples 8 through 12 are formed from LCP 1, LCP 2, another type of first liquid crystal polymer (“LCP 1b”), LDS concentrate, talc, and glass fiber. LCP 1b is formed from approximately 42.8% HBA, 8.6% TA, 28.6% HQ, and 20% NDA, and has a melting temperature of approximately 315°C. Specific formulations are described in more detail in Table 4 below.
[0076] Table 4: Formula
[0077]
[0078] The thermal properties, mechanical properties, and flame retardancy of samples 8-12 were tested. The results are presented in Tables 5-6 below.
[0079] Table 5: Thermal and Mechanical Properties
[0080]
[0081] Table 6: Unaged flame retardancy at 0.8mm
[0082]
[0083] These and other modifications and variations can be made to the invention by those skilled in the art without departing from the spirit and scope of the invention. Furthermore, it should be understood that aspects of the various embodiments can be interchanged entirely or partially. In addition, those skilled in the art will understand that the foregoing description is merely exemplary and is not intended to limit the invention as further described in the appended claims.
Claims
1. A polymer composition comprising a polymer matrix, wherein the polymer matrix comprises: at least one first liquid crystalline polymer, the first liquid crystalline polymer containing: aromatic dicarboxylic acid repeat units derived from 2,6-naphthalene dicarboxylic acid and optionally terephthalic acid, isophthalic acid, or a combination thereof; aromatic diol repeat units derived from hydroquinone, 4,4'-biphenol, or a combination thereof; and aromatic hydroxycarboxylic acid repeat units derived from 4-hydroxybenzoic acid, 6-hydroxy-2-naphthoic acid, or a combination thereof, wherein repeat units derived from 2,6-naphthalene dicarboxylic acid comprise from about 2 mol.% to about 30 mol.% of the first liquid crystalline polymer; at least one second liquid crystalline polymer comprising: aromatic dicarboxylic acid repeat units derived from 2,6-naphthalene dicarboxylic acid, terephthalic acid, isophthalic acid, or a combination thereof; aromatic diol repeat units derived from hydroquinone, 4,4'-biphenol, or a combination thereof; and aromatic hydroxycarboxylic acid repeat units derived from 4-hydroxybenzoic acid, 6-hydroxy-2-naphthoic acid, or a combination thereof, wherein repeat units derived from 2,6-naphthalene dicarboxylic acid comprise no more than about 0.5 mol.% of the second liquid crystalline polymer; wherein the ratio of aromatic diol repeat units of the first liquid crystalline polymer to aromatic diol repeat units of the second liquid crystalline polymer is from about 1 to about 8.
2. The polymer composition of claim 1, wherein the first liquid crystalline polymer, the second liquid crystalline polymer, or a combination thereof is obtained from recycled scrap.
3. The polymer composition of claim 1, wherein the first liquid crystalline polymer comprises from about 1 wt.% to about 50 wt.% of the polymer matrix, and the second liquid crystalline polymer comprises from about 50 wt.% to about 99 wt.% of the polymer matrix.
4. The polymer composition of claim 1, wherein the first liquid crystalline polymer comprises repeat units derived from terephthalic acid and / or isophthalic acid in an amount from about 1 mol.% to about 30 mol.%.
5. The polymer composition of claim 1, wherein the first liquid crystalline polymer comprises repeat units derived from hydroquinone and / or 4,4'-biphenol in an amount from about 5 mol.% to about 40 mol.%.
6. The polymer composition of claim 1, wherein the first liquid crystalline polymer comprises repeat units from 4-hydroxybenzoic acid in an amount from about 30 mol.% to about 80 mol.%.
7. The polymer composition of claim 1, wherein the second liquid crystalline polymer is free of aromatic dicarboxylic acid repeat units derived from 2,6-naphthalene di carboxylic acid.
8. The polymer composition of claim 1, wherein the second liquid crystalline polymer comprises repeat units derived from 6-hydroxy-2-naphthoic acid and / or 4-hydroxybenzoic acid in an amount from about 30 mol.% to 80 mol.%.
9. The polymer composition of claim 1, wherein the second liquid crystalline polymer comprises repeat units from hydroquinone and / or 4,4'-biphenol in an amount from 1 mol.% to about 30 mol.%.
10. The polymer composition of claim 1, wherein the polymer matrix comprises at least one third liquid crystalline polymer.
11. The polymer composition of claim 10, wherein the third liquid crystal polymer is present in an amount of about 1 wt.% to about 35 wt.% of the polymer matrix.
12. The polymer composition of claim 10, wherein the third liquid crystal polymer contains repeating units derived from 4-hydroxybenzoic acid and 6-hydroxy-2-naphthoic acid.
13. The polymer composition of claim 12, wherein the third liquid crystal polymer comprises repeating units derived from 4-hydroxybenzoic acid and repeating units derived from 6-hydroxy-2-naphthoic acid, wherein the amount of repeating units derived from 4-hydroxybenzoic acid is from about 40 mol.% to about 90 mol.%, and the amount of repeating units derived from 6-hydroxy-2-naphthoic acid is from about 10 mol.% to about 60 mol.%.
14. The polymer composition of claim 10, wherein the third liquid crystal polymer is obtained from recycled waste.
15. The polymer composition of claim 1, wherein the polymer matrix exhibits a melting temperature of about 240°C or higher.
16. The polymer composition of claim 1, wherein the polymer composition exhibits a load flexural temperature of about 150°C or higher.
17. The polymer composition of claim 1, wherein the polymer composition further comprises a filler.
18. The polymer composition of claim 17, wherein the filler comprises reinforcing fibers.
19. The polymer composition of claim 17, wherein the filler comprises particulate filler particles, flake mineral particles, mineral fibers, or combinations thereof.
20. The polymer composition of claim 17, wherein the filler comprises a laser-activated additive.
Citation Information
Patent Citations
Polymer underwater melt cutter and processes associated therewith
US20100102467A1
Polyester of 6-hydroxy-2-naphthoic acid and para-hydroxy benzoic acid capable of readily undergoing melt processing
US4161470A
Process for producing liquid crystal polymer
US5616680A
Process for producing liquid crystal polymer
US6114492A
Anisotropic melt-forming polymers having a high degree of stretchability
US6514611B1
